ANALYSIS OF TRANSPORT SERVICES PLANS OF REGIONS AND PROPOSALS FOR CHANGES IN REGIONAL TRANSPORT SERVICES PLAN (Perner's Contacts, 2013)
The analysis of transport services plans of all individual regions in the Czech Republic is made is the paper. The main problems of the plans are mentioned there in the paper. Proposals of changes in regional transport services plans are developed in accordance with this analysis. These proposals are divided into part of legislative changes and into part of own specific content of the plan.
Keywords: transport service; passenger transport; plan of transport services